Propolis Controlled Delivery Systems for Oral Therapeutics in Dental Medicine: A Systematic Review - Andressa da Silva Barboza; Juliana Silva Ribeiro de Andrade; Monika Lamas Ferreira; Carla Lucía David Peña; Juliê Silveira da Costa; André Ricardo Fajardo; Rafael Guerra Lund (MDPI AG, 2023)
This systematic review synthesizes the existing evidence in the literature regarding the association of propolis with controlled delivery systems (DDSs) and its potential therapeutic action in dental medicine. Two independent reviewers performed a literature search up to 1 June 2023 in five databases: PubMed/Medline, Web of Science, Cochrane Library, Scopus, and Embase, to identify the eligible studies. Clinical, in situ, and in vitro studies that investigated the incorporation of propolis as the main agent in DDSs for dental medicine were included in this study. Review articles, clinical cases, theses, dissertations, conference abstracts, and studies that had no application in dentistry were excluded. A total of 2019 records were initially identified. After carefully examining 21 full-text articles, 12 in vitro studies, 4 clinical, 1 animal model, and 3 in vivo and in vitro studies were included (n = 21). Relevant data were extracted from the included studies and analyzed qualitatively. The use of propolis has been reported in cariology, endodontics, periodontics, stomatology, and dental implants. Propolis has shown non-cytotoxic, osteoinductive, antimicrobial, and anti-inflammatory properties. Moreover, propolis can be released from DDS for prolonged periods, presenting biocompatibility, safety, and potential advantage for applications in dental medicine.